Endoscopic Ultrasound From Usual to Special - Chong, Charing (IntechOpen, 2017)
This book is oriented toward clinical studies in the field of endoscopic ultrasound. Due to the advancement in technology, resolution and development of accessory tools, the applications of endoscopic ultrasound have been widely extended. This book covers from usual to special applications of endoscopic ultrasound in various specialties. I hope this book can serve as a tiny telescope that shows how the techniques of endoscopic ultrasound can be used in various parts of the body.